Roots of Radical Sunni Traditionalism Fear of Reason and the Hashwiyah - Karim Douglas, Crow (2016)
Any positive forward-moving progress within Muslim societies necessitates the negative task of uncovering and dissipating obstacles to progress. An overview of the historical development of radical Sunni> Traditionalism summarizing its chief doctrinal preoccupations and motives, affords a deeper understanding of the contemporary dilemma facing Muslims. The H{ashwi>yah [ignoramuses] were literalists who apprehended merely the surface meaning of words and concepts. They represented an orientation with a core doctrinal basis centred in H{anbalite Traditionalism whose law and creed were anchored in a narrow textualism with anthropomorphic and determinist views. Research into the H{ashwi>yah’s doctrinal intolerance, hostility to rationalism, and mob tactics reveals the hallmark of deformist Islam. Contemporary Saudi H{anbalite religious ideology exhibits definite characteristics rooted in the ancient H{ashwi>yah worldview. Despite the small numerical and geographical footprint of H{anbalism today, the current amplification of a H{ashwi>-like mentality makes a deep imprint by virtue of its trans-national ubiquity. * While this study employs Arabic terms and concepts, we provide basic context and sufficient orientation as to be intelligible to novices in the study of Islam. It is part of a broader investigation into historical and ideological roots of religious teachings that have direct bearing on the global spread of bloodshed and militarism.